2003
DOI: 10.1046/j.1365-2109.2003.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian maturation of wild Farfantepenaeus paulensis in relation to histological and visual changes

Abstract: The present study describes the ovarian development stages of wild Farfantepenaeus paulensis (Pe¤ rez-Farfante) through the combined observation of histological and visual characteristics. Twenty-¢ve females (61.872.4 g) were captured in 35^40-m deep waters o¡ southern Brazil (271S). The females were grouped according to the size and shape of their ovary and then killed. The colour of the fresh ovary was compared with a chromatic scale catalogue. Analysis of the histological sections of each ovary determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 10 publications
7
59
0
3
Order By: Relevance
“…(Vogt et al, 1989;Castille & Lawrence, 1991;Tan-Fermin, 1991;Medina et al, 1996;Quintero & Garcia, 1998;Palacios et al, 1999). Recently, the investigations intending to classify the ovaries for fishery management purposes have suggested the simplification of the development stages, reducing it to only 4, named immature, developing, ripe and spent (Peixoto et al, 2003;Dumont et al, 2007). It does happen due to high similarity between developing and incipient maturity stages, which show similar stage of cell development, but slightly different organization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Vogt et al, 1989;Castille & Lawrence, 1991;Tan-Fermin, 1991;Medina et al, 1996;Quintero & Garcia, 1998;Palacios et al, 1999). Recently, the investigations intending to classify the ovaries for fishery management purposes have suggested the simplification of the development stages, reducing it to only 4, named immature, developing, ripe and spent (Peixoto et al, 2003;Dumont et al, 2007). It does happen due to high similarity between developing and incipient maturity stages, which show similar stage of cell development, but slightly different organization.…”
Section: Resultsmentioning
confidence: 99%
“…At least 15 ovaries, from each development stage, were sampled. A sample of ovarian tissue was collected from anterior part of gonad for histological sectioning since homogeneous development along the ovary has been reported for a similar species (Peixoto et al, 2003). Shape and color (Pantone, 1999) of ovaries were digitally recorded under the approximated same quantity of light, to establish a macroscopic classification validated by subsequent histological sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also indicated that females present a significantly higher relative frequency in larger size classes, which have been previously reported for P. schmitti populations (Santos et al, 2005(Santos et al, , 2008. Penaeid females are larger than males due to the body space needed for gonadal development (Hartnoll, 1982;Dall et al, 1990) and thus more abundant in larger size classes (García & Le Reste, 1986) Studies of ovarian development in penaeids have been used as a tool for the establishment of guidelines for fishery management (Quintero & Gracia, 1998), as well as the improvement of breeding technology for aquaculture operations (Peixoto et al, 2003;Dumont et al, 2007;Gonçalves et al, 2009;Machado et al, 2009). Histological analyses of the ovaries are considered to be one of the most accurate procedures for the determination of the maturational stage of female crustaceans (Ohtomi et al, 2003;Carbonell et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the supposedly advantageous performance of wild broodstock, the unpredictable supply and high capture costs might constrain the sustainable development of F. paulensis farming in the region. In this context, several studies have been carried out to optimize the maturation and reproduction of this species in captivity (Peixoto et al, 2002a(Peixoto et al, , 2002b(Peixoto et al, , 2003b(Peixoto et al, , 2003c(Peixoto et al, , 2004b, especially the evaluation of the domesticated broodstock as an alternative (Cavalli et al, 1997;Peixoto et al, 2003aPeixoto et al, , 2004a. The accelerated search to close the life cycle and improve the reproductive performance of F. paulensis in captivity will certainly contribute to the design of an efficient breeding program.…”
Section: Availability Of Plmentioning
confidence: 99%